Raf kinase inhibitor protein mediates intestinal epithelial cell apoptosis and promotes IBDs in humans and mice. Issue 4 (22nd January 2016) - Lin, Wenlong; Ma, Chunmei; Su, Fasheng; Jiang, Yu; Lai, Rongrong; Zhang, Ting; Sun, Kai; Fan, Liping; Cai, Zijian; Li, Zhongqi; Huang, He; Li, Jun; et al.
Abstract : Objective: Raf kinase inhibitor protein (RKIP) appears to control cancer cell metastasis and its expression in colonic tissue is related to colonic cancer development. We sought to identify the roles of RKIP in maintaining homeostasis of GI tract. Design: The expression of RKIP was determined by immunohistochemistry and western blot analysis. RKIP knockout and wild-type mice were administered dextran sulfate sodium (DSS) or 2, 4, 6-trinitrobenzenesulfonic acid (TNBS) to induce experimental colitis, and the mice were assessed based on colitis symptoms and biochemical approaches. The mechanism was analysed using immunoprecipitation and pull-down experiments. Results: The RKIP expression is positively correlated with the severity of IBD. RKIP deficiency protects mice from DSS-induced or TNBS-induced colitis and accelerated recovery from colitis. RKIP deficiency inhibits DSS-induced infiltration of acute-phase immune cells and reduces production of proinflammatory cytokines and chemokines in colon. RKIP deficiency inhibits DSS-induced or TNBS-induced colonic epithelial barrier damage and intestinal epithelial cell (IEC) apoptosis. RKIP deficiency also inhibits tumour necrosis factor-alpha-induced IEC apoptosis and colitis. Mechanistically, RKIP enhances the induction of P53-upregulated modulator of apoptosis by interacting with TGF-β-activated kinase 1 (TAK1) and promoting TAK1-mediated NF-κB activation. This is supported by the observation that TAK1 activation is positively correlated with the expression of RKIP in human clinical samples and the development of IBD. Conclusions: RKIP contributes to colitis development by promoting inflammation and mediating IEC apoptosis and might represent a therapeutic target of IBD.